A rare form of domestic accident: blast abdominal injury with evisceration of abdominal viscus - Basak, Aniruddha; Ghosh, Arindam; Mishra, Prafulla Kumar (International Journal of Contemporary Pediatrics, 2019)
Evisceration of abdominal viscus following “Flowerpot firecracker” (tubri) blast injury to the abdomen is a rare but dangerous form of domestic accident. Lack of knowledge and non-compliance of safety measures is the major reason for firecracker eventualities. A 10-year male child presented three hours post-injury with a wound over the upper abdomen. On examination there was evisceration of part of stomach along with colon through supraumbilical abdominal wound. Resuscitation and repair following exploratory laparotomy performed. Patient recovered well postoperatively. Public awareness and safety measures need to be taken to prevent the fatal outcomes of firecracker misuse.